The Implementation of Little Circle Arabic Learning to Improve Speaking Skills of Senior High School Students - Rahma, Hosita Laili; Murtadho, Nurul; Fauzi, Moh Fery (Institut Agama Islam Negeri Curup, 2024)
Speaking skills are one of the barometers of someone's proficiency in learning a foreign language. Consequently, speaking skills are being widely developed in madrasahs. However, most students experience the highest language anxiety in speaking skills, as seen in the case of 10th grade students at MA Nurul Ulum. Recognizing this fact, researchers have proposed a new innovation in the learning process through the implementation of the Little Circle Arabic Learning (LCAL) in teaching speaking skills. This study aims to improve students’ skills in speaking Arabic. The research utilizes the classroom action research method according to the theories of Stephen Kemmis and MC Taggart, conducted in two cycles (8 meetings), with four steps in each cycle: planning, action, observation, and reflection. The subjects of this study are 22 students from the 10th grade at MA Nurul Ulum. The results show an improvment in speaking skills due to the average score of speaking skills evaluation by 10.5 in cycle I, from 75.4 (C) to 85.9 (B). Then, Then the researchers made improvement and repair in the cycle II until it became there was a further increase of 5.6 to 91.5 (A). Therefore, the LCAL model can enhance the Arabic speaking skills of 10th grade students at MA Nurul Ulum.